On the Cauchy problem for a generalized Degasperis-Procesi equation. Issue 8 (10th June 2020) - Ye, Weikui; Yin, Zhaoyang
ABSTRACT: We first establish the local well-posedness for a generalized Degasperis-Procesi equation in nonhomogeneous Besov spaces. Then we present a global existence result for the equation. Moreover, we obtain a blow-up criteria and provide a sufficient condition for strong solutions to blow up in finite time.